Chartocerus hyalipennis (Hayat) (Hym: Signiphoridae), a gregarious hyperparasitoid on mealybugs (Hom.: pseudococcidae): biology and host range in west Africa - Goergen, Georg E.; Neuenschwander, Peter (1994)
The biology and behaviour of the signiphorid Chartocerus hyaipennis (HAYAT) were studied in the laboratory on Epidinocarsis lopezi (DE SANTlS), a parasitoid of the cassava mealybug Phenacoccus manihoti MATlLE-FERRERO. Only mummified secondary hosts, i.e. mealybugs, were accepted for ovi-position. Host feeding and oviposition always occurred on the same host. The females are proovigenic and produced more eggs the more hosts they fed upon. When they had access to hosts and honey they lived significantly longer than without host feeding. On average, 2-3 relatively large eggs were laid per host and the sex ratio was strongly female biased. Larvae passed through four instars. At 28°C development from egg to adult lasted 16.0 days. In West Africa, C. hyalipennis is a rather unspecific ectophagous hyperparasitoid with a host range of at least seven species of primary parasitoids, all encyrtids attacking various pseudococcids.